Factors Influencing Internet Gamblers' Use of Offshore Online Gambling Sites: Policy Implications. Issue 2 (18th July 2018) - Gainsbury, Sally M.; Abarbanel, Brett; Blaszczynski, Alex
Abstract : Gambling is a heavily regulated activity, but policies are difficult to enforce in the online context. While governments may attempt to restrict access to licensed providers only, consumers can access offshore sites, creating a potential risk of harm and reducing taxation. This article examines how consumers select Internet gambling sites, and the characteristics of those who use offshore as opposed to domestic sites. Past‐month Australian Internet‐gamblers (N = 1, 001, 57.2 percent male) completed an online survey. Participants responded to questions about their online gambling, including use of offshore sites, reasons for site selection, awareness of regulations, preferences for regulated sites, and gambling‐related problems. Offshore gamblers (52.7 percent) were a distinct demographic cohort, and were more highly involved in online gambling. Lack of awareness of gambling regulation did not sufficiently explain use of offshore gambling sites; rather, both groups had a relatively low concern for where a site was regulated, choosing sites instead based on ease of use, and cues that they were designed for gamblers in the advertised jurisdiction. Use of offshore gambling sites may be discouraged by focusing on the benefits of domestic sites and ensuring that these can provide a good consumer experience. Abstract : 摘要: 赌博是一项受到严厉管制的活动, 但相关监管政策很难在网络背景下实行。尽管政府可能会试图将这项活动限制为仅在许可供应商处进行, 但消费者可以登录境外网站进行赌博, 这便产生了潜在的危害风险、减少了税收。本文考察了消费者如何选择网络赌博网站, 以及使用境外而不是境内赌博网站的人群特征。过去一个月里澳洲网络赌博者(N = 1001, 男性占57.2 %)完成了一项网络调查。参与者对有关其网络赌博的提问做出了反应, 包括境外网站的使用、网络选取的原因、对监管政策的意识、对受监管网站的偏好、以及与赌博相关的问题。境外赌博者(52.7%)是一个独特的人群, 他们更喜欢介入网络赌博。赌博监管方面的意识缺失并不能完全解释他们(为何)使用境外赌博网站；相反, 使用境外网站或境内网站的赌博者相对而言都不太关心网站的监管地在哪, 他们选择网站时基于两点: 网站使用的容易度和"他们在管辖范围内被认为是赌博者"的消息提示。如果聚焦于境内网站的利益, 并保证境内网站能提供良好的消费者体验, 则境外赌博网站的使用可能会降低。 Abstract : Resumen: Las apuestas son una actividad altamente regulada, pero las políticas son difíciles de controlar cuando son en línea. Mientras que los gobiernos pueden restringir el acceso excepto para proveedores licenciados, los consumidores pueden tener acceso a sitios de apuestas en el extranjero, lo cual crea un riesgo potencial de daño y reducción de tributación. Este artículo examina cómo los consumidores seleccionan sitios de apuestas por Internet, y las características de aquellos que utilizan los sitios en el extranjero en vez de los sitios domésticos. El mes pasado, los apostadores por Internet australianos (N = 1001, 57.2 por ciento hombres) llenaron una encuesta por Internet. Los participantes respondieron preguntas acerca de sus apuestas por Internet, incluyendo el uso de sitios en el extranjero, razones por las que eligen los sitios, conocimiento de las regulaciones, preferencias por sitios regulados y problemas relacionados con las apuestas. Los apostadores que acuden a sitios en el extranjero (52.7 por ciento) eran un grupo demográfico particular y estaban más fuertemente involucrados en las apuestas por Internet. La falta de conocimiento de las regulaciones de apuestas no fue un factor que explicara completamente el uso de sitios de apuestas en el extranjero; más bien, ambos grupos no se preocuparon mucho por saber dónde estaba regulado un sitio y eligieron sitios que eran fáciles de usar y que parecían estar diseñados para usuarios en la jurisdicción promocionada. El uso de sitios de apuestas en el extranjero podría ser reducido al enfocarse en los beneficios de los sitios domésticos y asegurarse que estos puedan ofrecer una buena experiencia al consumidor.